2018
DOI: 10.1122/1.5024384
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of fumed silica nanoparticles/partially hydrolyzed polyacrylamide aqueous solutions under small and large amplitude oscillatory shear deformations

Abstract: Partially hydrolyzed polyacrylamide (HPAM) is one of the most widely used polymers for enhanced oil recovery operations. However, high temperature and high salinity in oil reservoirs restrict its functionality and performance. To alleviate this, incorporating fumed silica nanoparticles (NPs) in HPAM solutions was found to be very effective in harsh oil reservoir conditions to improve the efficiency of polymer flooding. Studying the flow behavior of hybrid polymer and fumed silica NP solutions under real reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 112 publications
2
24
0
Order By: Relevance
“…Oscillatory frequency sweeps have been widely used to characterize polymer filled samples (polymer composites, polymer solutions, etc.) [34,35]. Information about a sample's rigidity and network structure can be obtained by studying viscoelastic parameters, such as the storage modulus (G'), loss modulus (G'') and damping factor (tan δ) [36].…”
Section: Oscillatory Rheology Analysis Of Magnetic Paste Formulationsmentioning
confidence: 99%
“…Oscillatory frequency sweeps have been widely used to characterize polymer filled samples (polymer composites, polymer solutions, etc.) [34,35]. Information about a sample's rigidity and network structure can be obtained by studying viscoelastic parameters, such as the storage modulus (G'), loss modulus (G'') and damping factor (tan δ) [36].…”
Section: Oscillatory Rheology Analysis Of Magnetic Paste Formulationsmentioning
confidence: 99%
“…Additionally, as the strain amplitude and frequency can be controlled independently, LAOS flow covers a wide spectrum of nonlinear situations with respect to time and deformation. 17,18 Considering the aforementioned reasons, over the past decade, LAOS has been extensively employed to study nonlinear viscoelasticity to detect any changes in topology, morphology, concentration, and so forth in a variety of systems, such as polymer solutions, 19,20 polymer nanocomposites, 21 and polymer hydrogels. 22 The LAOS approach provides an extensive framework to detect intracycle nonlinearities, providing vital information for the structure−property relationship of the filler−polymer systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, based on the strain sweep test data (see Figure 11D), the order of the critical strain amplitude γ c (strain at which linear to nonlinear transition occurs, see the arrows in Figure 11D) of the samples is as follow: γ c,PVDF/clay > γ c,PVDF/clay/CNT > γ c,PVDF/CNT . In our previous works, [ 72‐76 ] we demonstrated that the stronger the nanofillers' network, the smaller γ c . Hence, the rigid network structure of the binary PVDF/N‐CNT nanocomposite is more sensitive to the applied deformation.…”
Section: Resultsmentioning
confidence: 81%